2019
DOI: 10.1590/1517-869220192504174345
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile, Functional Capacity and Ankle-Brachial Index in Active Older Adults

Abstract: Introduction: Regular physical activity prevents cardiovascular diseases (CVD) and atherosclerosis, in addition to improving lipid levels and functional capacity in older adults. Objective: To evaluate and compare the lipid levels, functional performance and ankle brachial index (ABI) of sedentary and active older adults. Methods: This was a comparative cross-sectional study with 84 elderly (≥60 years) male and female subjects, divided into two groups: sedentary group (SG, n = 50) and active group (AG, n = 34)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
2
0
1
Order By: Relevance
“…Lipoprotein disturbances have also been associated with increased CV risk [48,49] and ABI is a marker of systemic atherosclerotic vascular disease [50]. In fact, the association between low ABI and increased cardiovascular mortality risk is well established, indicating that the ABI measurement is an important tool for diagnosing PAD and for monitoring vascular commitments, as well as for predicting myocardial infarction [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Lipoprotein disturbances have also been associated with increased CV risk [48,49] and ABI is a marker of systemic atherosclerotic vascular disease [50]. In fact, the association between low ABI and increased cardiovascular mortality risk is well established, indicating that the ABI measurement is an important tool for diagnosing PAD and for monitoring vascular commitments, as well as for predicting myocardial infarction [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…According to total fat percentage it is important to highlight that this is directly associated to the lipid profiled (LP) [66] where active older have better LP compare to sedentary older [67]. Due to the RE, the total fat percentage is reduced and lot of elderly individuals research showed it [19,23,68].…”
Section: Discussionmentioning
confidence: 99%
“…Estas doenças aumentam significativamente a procura por atendimento médico e maior dependência de terceiros quando em idades avançadas (9) . Atualmente as doenças cardiovasculares são as principais causas de óbitos no Brasil e no mundo (7)(8)10) . Apesar dos alunos demonstrarem conhecimento dos possíveis benefícios físicos e sociais da atividade física, como por exemplo, o aumento da capacidade de concentração, rendimento acadêmico e maior perseverança na realização de tarefas, alguns estudos com universitários demonstram a diminuição na prática da atividade física após o ingresso à universidade (1)(2)(3) .…”
Section: Introductionunclassified